Industrial Discipline in the Canadian Federal Jurisdiction - Eden, Genevieve (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1993)
This study involves an analysis of adjudicator decisions dealing with complaints of unjust dismissal from nonunionized workers in the Canadian federal jurisdiction to determine the approach adopted with respect to industrial discipline. The analysis includes all disciplinary decisions rendered between the enactment of the legislation in 1978 to March 1989 (279 cases). The results, based on logit analysis, reveal that adjudicators have adopted the approach to discipline by arbitrators in the unionized sector. The definition, application, and purpose of discipline espoused by adjudicators are also discussed. The author questions the adoption of this principle given the potential negative effects of discipline as illustrated in the organizational behavior literature.